Anisotropy of elastic deformations in multilayer (In,Ga)As/GaAs structures with quantum wires: X-ray diffractometry study - Strelchuk, V.V.; Kladko, V.P.; Yefanov, O.M.; Kolomys, O.F.; Gudymenko, O.I.; Valakh, M.Ya. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
Using the method of high-resolution X-ray diffraction (HRXRD), we have studied 17-period In₀.₃Ga₀.₇As/GaAs multilayer structure with self-assembled quantum wires (QWRs) grown by the MBE and subjected to postgrowth rapid thermal annealing (RTA) at temperatures (Tann) from 550 to 850 °C for 30 s. It has been shown that the spatial arrangement of QWRs (lateral and vertical) causes the quasi-periodical strain distribution, the strains being essentially anisotropic relatively to crystallographic directions of 〈011〉 type. At Tann ≤ 750 °С, the driving mechanism of structural transformations is relaxation of residual strains due to thermally-activated and strain-enhanced processes of In/Ga atom interdiffusion at the interface QWRs-2D layer, which does not result in considerable changes of the In concentration in (In,Ga)As QWRs. The presence of two superlattice vertical periods in the samples under study and their changes during RTA we explained by an anisotropic character of elastic strain distribution and lowered structure symmetry. The revealed increase in the (In,Ga)As QWRs lateral period caused by RTA is a direct evidence of running lateral mass-transfer processes and can be explained using the model “nucleation plus strain-enhanced In/Ga atom lateral interdiffusion”. At low annealing temperatures, there takes place dissolution of intermediate QWRs as a result of interdiffusion enhanced by residual anisotropic strains. At high RTA temperatures, the interdiffusion process is mainly determined by the composition gradient existing between QWRs and 2D layer.